In vivo hypoxic preconditioning protects from warm liver ischemia-reperfusion injury through the adenosine A2B receptor - Choukèr, Alexander; Thiel, Manfred (Transplantation, 2012)
Background Liver ischemia-reperfusion injury (IRI) is a known risk factor for the postoperative outcome of patients undergoing liver surgery/transplantation. Attempts to protect from organ damage require multidisciplinary strategies and are of emerging interest in view of patients with higher age and American Society of Anesthesiology status. Ischemic preconditioning has been successfully applied to prevent from IRI during liver resection/transplantation. Because even short periods of ischemia during preconditioning inevitably lead to hypoxia and formation of anti-inflammatory/cytoprotective acting adenosine, we reasoned that short nonischemic hypoxia also protects against hepatic IRI. Methods Mice underwent hypoxic preconditioning (HPC) by breathing 10% oxygen for 10 min followed by 10 min of 21% oxygen before left liver lobe ischemia (45 min) and reperfusion (4 hr). The interactions of hypoxia→adenosine→adenosine receptors were tested by pharmacologic antagonism at adenosine receptor (AR) sites in wild-type mice and in mice with genetic deletions at the A1, A2A, A2B, and A3 ARs. Hepatocellular damage, inflammation, and metabolic effects were quantified by enzyme activities, cytokines, liver myeloperoxidase, blood adenosine, and tissue AMP, respectively.Results Hepatoprotection by HPC was significant in wild-type and A1, A2A, and A3 AR knockout mice as quantified by lower alanine aminotransferase serum activities, cytokine levels, histologic damage scores, tissue myeloperoxidase concentrations, and preserved AMP concentrations. Protection by HPC was blunted in mice pretreated with the A2B AR antagonist MRS1754 or in A2B AR knockout mice. Conclusions Because liver protective effects of HPC are negated when the A2B receptor is nonfunctional, the hypoxia→adenosine→A2B receptor pathway plays a critical role in the prevention of warm IRI in vivo. Hypoxic activation of this pathway warrants use of selective A2B AR agonists or even intermittent hypoxia (e.g., in deceased organ donors) to protect from liver IRI.